Application of EPC internet of things and radio frequency identification technology in logistics. (26th November 2021) - Wang, Xiaobei; Wang, Yaya
This paper focuses on the practical application of EPC and RFID technology in the logistics. Internet is the foundation of IoT, it using wireless communications, RFID, computer network technology etc, construct a huge system that covers the world. In order to meet the identification and efficient identification of individual products, the Automatic Identification Laboratory of the Massachusetts Institute of Technology proposed the concept of EPC, in which each item is assigned a unique identification code. The EPC code is stored in an electronic tag of a silicon chip, and the tag is attached to the identified article. When an EPC tag is embedded in an item, the item and the product electronic code in the EPC tag are in one-to-one correspondence. It is identified, transmitted, and queried by high-level information processing software. On the basis of the internet, a logistics model that provides various information services for the supply chain is formed.